A comparative study on the seismic performance of RC beam-column joints retrofitted by ECC, FRP, and concrete jacketing methods. (1st April 2023) - Hung, Chung-Chan; Hsiao, Hsin-Jui; Shao, Yi; Yen, Cheng-Hao
Abstract: Reinforced concrete (RC) beam-column joints in many old buildings do not have appropriate seismic detailing that allows them to provide sufficient strength and stiffness in strong seismic events. To improve the seismic performance of these deficient beam-column joints, this study proposes a new retrofitting method based on high-strength steel bar mesh and Engineering Cementitious Composite (ECC), a fiber-reinforced cementitious material that shows high tensile ductility and damage tolerance. The proposed method reduces the required size of the retrofitting jacket through the combined use of ECC jackets and high-strength steel bar mesh. The performance of the proposed ECC jacketing method was compared with that of concrete jackets and fiber-reinforced-polymer (FRP) jackets. Experimental program included cyclic testing of four exterior beam-column joints, i.e., one control specimen and three others retrofitted using ECC, concrete, and FRP jacketing. Results showed that (1) reinforced ECC jackets confined the joint core and prevented localized damage in the joint zone via formation of dense and fine cracks, (2) the beam-column joint retrofitted using ECC jackets with high-strength steel mesh exhibited the favorable beam flexural failure, while the other three joints showed joint shear failure, (3) compared to other two retrofitting methods, the reinforced ECC jacket more effectively increased the strength, stiffness retention, energy dissipation capacity, deformation capacity, and collapse drift. In addition to experimental study, suitable strength models were suggested to evaluate the strength and failure patterns of the retrofitted exterior beam-column joints. Highlights: The combined use of ECC jackets and high-strength steel bar mesh for retrofitting joints. ECC jacketing transformed the joint shear failure to beam flexural failure. Tension stiffening of ECC was beneficial in controlling stiffness degradation of joints. ECC jackets were more effective than FRP and conventional concrete for retrofitting joints. Strength models were suggested to design and evaluate the retrofitted beam-column joints.